Polyphemus, Galatea, Heracles: Myths of Origin for Northern Groups - Lampinen, Antti (Suomen Ateenan Instituutin Säätiö, 2026)
This chapter explores the ways in which Greeks – and Romans, too, often modelling their stories on the Greek ones – conceptualised different northern groups through divine, heroic or monstrous genealogies and origin stories. These were a very potent and cognitively efficient way of ‘marking’ the northerners; frequently, they were used to explain the origin of purported northern characteristics, as well as making these groups, their customs, and their place in the world familiar or at least comprehensible. This was particularly common in the Hellenistic era, when the first shock of the Galatian or Gallic threats brought to the foreground the need to localise and circumscribe these newly important barbarian groups. Some of the myths and connection-building techniques were already well-established, and this chapter will thus begin from the important role of the Herodotean Scythians and Thracians. It is hypothesised that they would have wielded a formative influence on the subsequent tradition of writing about the North.
Marking the North. The Greek Tradition and Its Influence in the Roman Period